Egg white protein polymer: an affinity matrix for protease enrichment and isolation. Issue 1 (2nd January 2022) - Menfaatli, Esra; Zihnioğlu, Figen
ABSTRACT: Egg white was precipitated with acetone and cross-linked with glutaraldehyde. Protease specificity of the polymer was investigated with different types of proteases and non-protease proteins. Protein polymer effectively bound trypsin, papain and the different proteases from pancreatin. SDS-PAGE results and diffusion agar plate tests supported the protease-binding efficiency of the polymer. In conclusion, egg white protein polymer can specifically bind proteases and it is a convenient and cost-effective material for enrichment, isolation, and removal of proteases.